Comparative epidemiology, phylogenetics, and transmission patterns of severe influenza A/H3N2 in Australia from 2003 to 2017. Issue 6 (17th June 2020) - Xia, Jing; Adam, Dillon C.; Moa, Aye; Chughtai, Abrar A.; Barr, Ian G.; Komadina, Naomi; MacIntyre, C. Raina
Abstract: Background: Over the last two decades, Australia has experienced four severe influenza seasons caused by a predominance of influenza A (A/H3N2): 2003, 2007, 2012, and 2017. Methods: We compared the epidemiology, genetics, and transmission dynamics of severe A/H3N2 seasons in Australia from 2003 to 2017. Results: Since 2003, the proportion of notifications in 0‐4 years old has decreased, while it has increased in the age group >80 years old ( P  < .001). The genetic diversity of circulating influenza A/H3N2 viruses has also increased over time with the number of single nucleotide polymorphisms significantly ( P  < .05) increasing. We also identified five residue positions within or near the receptor binding site of HA (144, 145, 159, 189, and 225) undergoing frequent mutations that are likely involved in significant antigenic drift and possibly severity. The Australian state of Victoria was identified as a frequent location for transmission either to or from other states and territories over the study years. The states of New South Wales and Queensland were also frequently implicated as locations of transmission to other states and territories but less so over the years. This indicates a stable but also changing dynamic of A/H3N2 circulation in Australia. Conclusion: These results have important implications for future influenza surveillance and control policy in the country. Reasons for the change in age‐specific infection and increased genetic diversity of A/H3N2 viruses in recent years should be explored.